Efektivitas Kompres Daun Dadap Serep (Erythrina Lithosperma Miq) Dan Kompres Lidah Buaya (Aloe Vera Linn) Terhadap Bendungan ASI - Lestari, Ika Widdya (Jurnal Bahana Kesehatan Masyarakat (Bahana of Journal Public Health), 2025)
Background: Breast engorgement caused by milk dams will result in reduced milk production. This happens because the venous and lymphatic flow is blocked by breast milk, hindering the process of emptying the breast. If this condition is not treated immediately, the potential for more serious health problems such as breast abscesses will be inevitable. Curd leaf and aloe vera gel contain tannin compounds that can act as anti-inflammatory, reduce inflammation, and pain due to breast milk obstruction. The purpose of the study was to determine the effectiveness of curd leaf compresses and aloe vera compresses on breast milk dams. Research Methods: This study applied a quasi-experimental method with pretest-posttest treatment. Breast swelling scale assessment was carried out with the SPES table. The study population was 124 respondents with a sample of 30 respondents using accidental sampling technique. The research instrument used an observation sheet. Data analysis used Wilcoxon non-parametric test and Mann Whitney test.. Results: The results of the study showed that there was a difference in breast swelling scale before and after being given the intervention of aloe vera compress and aloe vera compress. Mann Whitney test in the aloe vera compress group resulted in a mean rank of 20.60, while in the spare curd leaf compress group it was 10.40. Conclusion: Aloe vera compresses are more effective in overcoming breast milk dams than spare leaves compresses.